Portrayal of Women as Victims in Mahesh Dattani‟s Tara, Thirty Days in September and Beneath the Rubble - Marigold , Vinita; Unius Backiavathy, Helen (International Journal of Psychosocial Rehabilitation, 2020)
The image of motherhood is depicted as a loving nurturer, caregiver, and protector. This image is subject to celebration and valorization in many societies, particularly in Indian society, where the image is deeply entrenched within notions of culture and tradition. A mother is depicted as one who is at the disposal of her children, who willingly endures pain and hardship for the sake of the family, and who willingly makes sacrifices to ensure her children’s well-being and happiness. Motherhood is iconized, and this is a major device of patriarchal control to which a girl child is exposed from early childhood. Mahesh Dattani, in his representation of the mothers in Tara and Thirty Days in September, projects fractured images that subvert the conventional portrayal of motherhood, enabling women to appear like living, breathing beings as prone to weakness and frailty as everyone else.